Hinweise für Prognose- und Abwehrmaßnahmen gegen Otiorrhynchus niger Fabricius und Hylobius abietis Linnaeus. - Rohde, Katharina (Contributions to Entomology = Beiträge zur Entomologie, 1966)
It was proposed to find methods of concentrating the rarely visible imagos of two in-jurious species of weevils for improved protection and control. In the case of Otiorrhynchus niger Fabricius this could be done by planting alder (Alnus glutinosa Gaertner) as decoy tree. Following the osmotactic behaviour of Hylobius abietis Linnaeus an assortment of odoriferous substances was arranged which should be tested. Alluring scents should be used to impregnate the trapping bark, and young plants should be treated with repellent scents.